A Feasibility Study to Assess the Effectiveness of Safe Dates for Teen Mothers. Issue 6 (14th October 2014) - Herrman, Judith W.; Waterhouse, Julie K.
ABSTRACT Objective: To determine the effectiveness of the adapted Safe Dates curriculum as an intervention for pregnant and/or parenting teens to prevent teen dating violence (TDV). Design: This pre‐/posttest, single‐sample study provided a means to assess the effectiveness of an adapted Safe Dates curriculum for teen mothers. Setting: The adapted Safe Dates curriculum was implemented in three schools designed for the unique needs of teens who are pregnant and/or parenting. Participants: The final sample of 41 teen participants, with a mean age of 16.27, completed 80% of the curriculum and two of the three assessments. Most of the teens were pregnant during participation in the curriculum, and six had infants between age 1 and 3 months. Methods: The teen mothers completed the pretest, participated in the 10‐session adapted Safe Dates curriculum, and completed the posttest at the end of the program and 1 month after program completion. The pre/posttest was adapted from the Safe Dates curriculum‐specific evaluation instrument. Senior, undergraduate nursing students were trained in and implemented the curriculum. Results: Participation in the adapted Safe Dates program yielded significant differences in the areas of responses to anger, gender stereotyping, awareness of resources for perpetrators and victims, and psychological violence perpetration. Conclusions: This adapted program may be effective in changing selected outcomes. The implementation of a larger scale, experimental/control group study may demonstrate the program's efficacy at reducing the incidence of TDV among teen mothers.